THE EFFECTIVENESS OF REGIONAL DISTRIBUTION ON PUBLIC WELFARE OF HASUNDUTAN HUMBANG DISTRICT - Darmo Hasugian; Sirojuzilam; Rujiman (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Humbang Hasundutan is a district located in North Sumatra Province . Before the division of the region, Humbang Hasundutan was still a capital city in Tarutung, North Tapanuli Regency and all administrations were centered in North Tapanuli Regency. After the division of the region in 2002, Humbang Hasundutan District began to focus on development and community welfare. Then the study aims to analyze effectiveness of regional divisions on economic growth Humbang Hasundutan the terms of the Gross Regional Domestic Product (PDRB) and for analyze effectiveness of regional divisions in community welfare Humbang Hasundutan. The research method used is descriptive quantitative. Using data collection techniques with interviews, observation, and documentation. The results of the study show that the division of the Humbang Hasundutan district from North Tapanuli district as the parent district shows that it is effective when viewed from economic growth (PDRB ADHK). Then based on the average difference test or Paired Sample Test, it shows the effectiveness of regional expansion on economic growth before and after the expansion of Humbang Hasundutan Regency that the significance value is 0.030 <0.05, it can be concluded that there are differences in Humbang Hasundutan district before and after regional expansion on economic growth or hypotheses received. The division of Humbang Hasundutan district from North Tapanuli district as the main district has effectively influenced the welfare of the people of Humabang Hasundutan district with welfare indicators, namely human development index (IPM), poverty, population and unemployment. human development index (IPM) regression coefficient (X1) of 1.87 percent, poverty regression coefficient (X2) of 0,92 percent, regression of the total population coefficient (X3) of 1,68 percent and regre the Unemployment coefficient (X4) of -0,194 percent.